Patrons and Clients Godfathers and the Democratization Process in Nigeria’s Fourth Republic (2023)
Godfatherism as a phenomenon has been in existence since time immemorial and continues to feature in many human endeavors. It is a sui gener is practice that depicts political might, political survival and power sustenance. In Nigeria, it indicates political relevance and significance that guarantees meteoric rise in political careers. This dominant political culture has been sustained by a privileged few that have held sway over the political directions and fortunes within Nigeria’s polity. Drawing case studies from Northern and Southern Nigeria, this study explores the characteristics of presumed godfathers in Nigeria’s political sphere. It details the basic information about godfathers, their ideology, the goals that inform their kind of politics and their primor¬dial engagements with the phenomenon. The study has major policy implications for the seemingly uneven gradation that party politics has assumed in Nigeria.